Macroeconomic Factors and Stock Market Performance in Nepal - Shrestha, Purna Man; Lamichhane, Pitambar (PYC Nepal Journal of Management, 2021)
This paper examines co-integrating relationship between macroeconomic factors and stock market performance in Nepal using time series data for the period 1987/88 to 2019/20. This study has used Autoregressive Distributed Lag (ARDL) bounds testing approach to identify the co-integrating relationship between macroeconomic variables and stock market performance. The stock market performance is measured by market capitalization which is considered as dependent variable and selected macroeconomic factors such as broad money supply measured by M2, economic growth measured by gross domestic product (GDP) and interest rate measured by 91-days Treasury bill rate are considered as explanatory variables. ARDL bounds test reveals that stock market performance is co-integrated with macroeconomic variables. Similarly, result of this paper shows the significant positive impact of economic growth. Further, finding reports a significant negative effect of broad money supply and interest rate on performance of Nepalese stock market in long-run. Finally, this paper concludes that disequilibrium of stock market performance in short-run is corrected by GDP, M2 and IR in the long-run. The policy implication of this paper is in formulation of capital market policy, monetary policy, financial policy and economic policy. Stock market policy makers should consider macroeconomic variables while formulating capital market policy for the better performance of stock market in Nepal.